2022
DOI: 10.1093/bioinformatics/btac594
|View full text |Cite
|
Sign up to set email alerts
|

Manifold classification of neuron types from microscopic images

Abstract: Analysis of cell types is recognized as a major task in current single cell genotyping and phenotyping. In neuroscience, 3-D neuron morphologies are often reconstructed from multi-dimensional microscopic images. Recent studies indicate that neurons could form very complicated distributions in the feature space, and thus they can be explored using manifold analysis. We have developed manifold-classification toolkit (MCT) software to replace the conventional clustering analysis to discover cell subtypes from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The first is the generation of connectivity associated t-type, e-type, and m-types data. A second step is building a thorough statistical model of all such data to mine the associations and distribution patterns, which could be homogeneous clusters or globally nonlinear manifold patterns (Liu and Qian, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The first is the generation of connectivity associated t-type, e-type, and m-types data. A second step is building a thorough statistical model of all such data to mine the associations and distribution patterns, which could be homogeneous clusters or globally nonlinear manifold patterns (Liu and Qian, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These neurons extend dozens of millimeters (Figure 4). It has been often observed that different neuron classes are poorly discriminated by global morphology where features such as length and branching number are considered (Liu & Qian, 2022;Peng et al, 2021). To overcome this limitation, we registered the whole set to CCFv3 using mBrainAligner.…”
Section: Detecting Primary Distributions and Key Morphological Variab...mentioning
confidence: 99%
“…Understanding how the interconnections of neurons account for brain functions has been a great pursuit over the past decades [Eichler et al, 2017, Lichtman and Denk, 2011, Liu and Qian, 2022, Dey et al, 2022, Wang et al, 2022. A brain circuit network refers to a physical map of a brain's structural connections, commonly referred to as a connectome.…”
Section: Introductionmentioning
confidence: 99%